Old Drugs, New Roles: Non-Cardiac Uses of Beta-Blockers – An Updated Systematic Review - Brynczka, Izabela; Jezierski, Michał; Nowicka, Ewelina; Patrzykąt, Klaudia Martyna; Gorzoch-Burduk, Zofia; Puzio, Julia; Marcinkowska, Paula; Krzyżaniak, Marta; Popielarska, Kinga; Wróblewska, Kamila (Quality in Sport, 2025)
Background: β-adrenergic blockers have long been used in cardiovascular medicine, yet growing evidence shows therapeutic potential beyond cardiac disease. Their pleiotropic effects—ranging from modulation of sympathetic signaling to anti-angiogenic and immunomodulatory actions—have increased interest in non-cardiac applications and drug repurposing. Aim: To review non-cardiac roles of β-blockers, summarize recent findings (2020–2025), compare mechanisms across indications, and highlight emerging oncologic and immunomodulatory uses. Material and Methods: This narrative review was based on PubMed, Google Scholar and Scopus searches (2020–2025) using terms including “beta-blockers”, “propranolol”, “timolol”, “repurposing”, “glaucoma”, “hemangioma” and “oncology”. Randomized trials, cohort studies, translational basic research and meta-analyses were included; studies without relevance to non-cardiac mechanisms or lacking extractable data were excluded. Results: Non-selective β-blockers remain essential in portal hypertension, reducing portal pressure and preventing bleeding. In infantile hemangioma, oral propranolol is more effective than topical timolol, with early initiation predicting better outcomes. Propranolol, timolol and metoprolol are effective in migraine prophylaxis, while propranolol remains first-line therapy for essential tremor. Timolol is a cornerstone glaucoma treatment, lowering intraocular pressure and delaying progression from ocular hypertension. In oncology, propranolol shows preclinical activity against proliferation, angiogenesis and immunosuppression, though clinical evidence is inconsistent. Conclusions: β-blockers represent a versatile drug class with established non-cardiac indications and promising emerging applications, especially in oncology. Their safety and broad mechanistic profile support further repurposing, but high-quality prospective trials remain necessary.